THE NEGOTIATIVE INTERRELATION BETWEEN THE VALUES OF ISLAMIC EDUCATION AND LOCAL CULTURE OF MULTICULTURAL COMMUNITY - Ifa Nurhayati (Universitas Islam Malang, 2022)
This article aims to analyze the social construction of Tengger tribe community towards the values of Islamic education in the midst of local culture diversity. This study was done in Ngadas village, Bromo. The theoretical approach used in this article is Berger and Luckman's social construction theory, while the data collection techniques were observation, interview, and documentation. In the research findings, it is found that three entities of external elements become the attraction of the community, namely a) exemplary behavior of Islamic figures, b) contextual approach in understanding religious teaching by Islamic figures, and c) strategies and media for preaching namely socio-cultural-psychological strategy and socio-spiritual-magical strategy. Second, at the moment of objectification, local communities continuously interact with Islamic education values because they feel that Islamic values have been naturally institutionalized to the community needs. Meanwhile, at the moment of internalization, three typologies were found as a result of community self-identification of Islamic education values, namely a) normative-theological-conservative, b) sociological-pragmatic-calculative, and c) sociological-empirical-intuitive.Keywords: Local wisdom, multicultural, Conservative, Pragmatic, Intuitive